Hormonal mechanisms of women’s risk in the face of traumatic stress - Jennifer S. Stevens; Madeline Davis; Cecilia A. Hinojosa; Rebecca Hinrichs; Alyssa R. Roeckner; Katelyn I. Oliver; Linzie Taylor; Justin L. C. Santos; Helena Zeleke; Esther Lin; Kristina Dahlgren; Timothy D. Ely; et al. (Proceedings of the National Academy of Sciences, 2025)
Women are underrepresented in biomedical research, limiting understanding of their disproportionate rates of stress-related disorders. Although men experience more trauma, women are twice as likely to develop posttraumatic stress disorder (PTSD). We tested whether ovarian hormones contribute to this disparity via their influence on threat-related brain activity. In a randomized, double-blind crossover study of 110 young women, we examined how exogenous estradiol (E2) modulates threat neurocircuitry, timed precisely to ovarian phase. E2 increased engagement of the ventromedial prefrontal cortex and, in the early luteal phase, reduced central and corticomedial amygdala reactivity to threat in women with little trauma history, but not those with PTSD. Fluctuations in E2 therefore modulate neural responses to threat, and sensitivity to these fluctuations may underlie women’s heightened vulnerability to stress-related disorders.